Integration of Strategic Management and Humanistic Education in Developing Student Character at MA Negeri 1 Nganjuk - A Wathon; Agus Zaenul Fitri; Sulistyorini Sulistyorini (PALAPA, 2025)
This study addresses the limited research on the integration of strategic management and humanistic education within Indonesian Islamic secondary schools, despite the significant potential of their synergy in fostering holistic character development. While previous research has examined character education, school leadership, or humanistic pedagogy in isolation, few have explored how these elements function together within a unified framework—particularly in the context of Madrasah Aliyah. The objective of this study is to analyze how strategic management supports and enhances humanistic educational practices, evaluate the impact of this integration on various dimensions of student character, and identify key sustaining factors at MA Negeri 1 Nganjuk. Utilizing a sequential explanatory mixed-methods design, the study commenced with quantitative surveys followed by qualitative interviews and document analysis. Participants included 150 students, 20 teachers, and 5 administrators selected through stratified random and purposive sampling. Quantitative data were analyzed using descriptive statistics, ANOVA, and multiple regression, while qualitative data were thematically interpreted. The findings reveal a significant positive relationship between the integration of strategic management and humanistic education and the development of student traits such as empathy, responsibility, integrity, and religious devotion. Strategic vision, effective resource allocation, and supportive leadership emerged as critical enablers of a humanistic and student-centered educational environment. The study concludes that this integration is vital for nurturing well-rounded character in Islamic schools, offering both theoretical contributions to the discourse on educational leadership and practical guidance for policy formulation, school governance, and curriculum design. It also recommends future longitudinal and comparative studies to further explore the long-term effects and broader applicability of this integrative approach.